Implementation of energy efficiency system in office buildings / Norashikin Abu Bakar - Abu Bakar, Norashikin (Faculty of Architecture, Planning and Surveying, 2010)
The dissertation is to study on energy efficiency system at office buildings. Energy efficiency is one of elements green building. Nowadays, an energy saving bring a new fenomena in Malaysia because government has spent lots of money and effort in implementing this building concept in order to support the global challenge in combating global warming. The country could spent less money on constructions of hydroelectric, electrical grids and other high cost energy producing methods thus using less natural resources such as the gas and petroleum. In this study, the objectives of this dissertation will be setting first. The objective of this dissertation is to focusing on system of energy efficiency used at office buildings. From this objective, details informations of green building, energy efficiency and commercial building are being explained based on the literature review in chapter two. Then, research methodology in chapter three is discuss about a continuous steps to complete this dissertation.